КУЛЬТУРА МІКРОВОДОРОСТЕЙ ЯК МОДЕЛЬНИЙ ОБ'ЄКТ В ГІДРОЕКОЛОГIЇ - Тренкеншу, Р. П. (Marine Ecological Journal, 2023)
Some approaches and methods applied to the solutions of problems related to the study of microalgae growth in culture have been considered. Possibilities to apply similar conceptual and formal apparatus in hydroecological investigations have been shown. To illustrate solutions of some problems of biokinetics, microevolution, population dynamics and microalgae photosynthesis, several examples have been given. Characteristics of microalgae growth in flow culture which is an open system in itself have been considered in detail. An example of the experimental data analysis applying magnitudes of reduced values for limiting factors and normalized values for output photosynthesis characteristics of microalgae have been given. The analysis allows to estimate the organization of the limiting link (bottle neck) in the chain of chemical reactions determining the organism growth. Introduction of concepts of efficient growth rate and ecopotential allows to estimate driving forces and direction of evolution of systems including microalgae and environment.